2014
DOI: 10.1016/j.actbio.2014.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NELL1 gene overexpression in iPSC-MSCs seeded on calcium phosphate cement

Abstract: Human induced pluripotent stem cell-derived mesenchymal stem cells (iPSC-MSCs) are a promising source of patient-specific stem cells with great regenerative potential. There has been no report on NEL-like protein 1 (NELL1) gene modification of iPSC-MSCs. The objectives of this study were to genetically modify iPSC-MSCs with NELL1 overexpression for bone tissue engineering, and investigate the osteogenic differentiation of NELL1 gene-modified iPSC-MSCs seeded on Arg-Gly-Asp (RGD)-grafted calcium phosphate cemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 58 publications
7
24
0
Order By: Relevance
“…Previous studies in vitro have shown that macroporous CPC scaffolds (with different formulation) support cell viability and differentiation of human mesenchymal stem cells (MSCs; Vater et al, ; Weir & Xu, ), and grafts of CPC scaffolds seeded with human MSCs promote skeletal regeneration in animal models (Chen et al, ), with good prospects for future developments and clinical applications. To overcome the limitations associated with isolation and poor regeneration potential of adult stem cells, researchers have recently explored the possibility to use human pluripotent stem cells as source of mesenchymal progenitors for bone engineering applications (Idowu, Cama, Deb, & Di Silvio, ; J. Liu, Chen, Zhao, & Xu, ; X. Liu, Wang, et al, ; Sladkova et al, ; Wang et al, ). In particular, human induced pluripotent stem cells (iPSCs) can be derived from every patient, proliferate indefinitely, and give rise to all cells constituting the bone tissue (Takahashi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies in vitro have shown that macroporous CPC scaffolds (with different formulation) support cell viability and differentiation of human mesenchymal stem cells (MSCs; Vater et al, ; Weir & Xu, ), and grafts of CPC scaffolds seeded with human MSCs promote skeletal regeneration in animal models (Chen et al, ), with good prospects for future developments and clinical applications. To overcome the limitations associated with isolation and poor regeneration potential of adult stem cells, researchers have recently explored the possibility to use human pluripotent stem cells as source of mesenchymal progenitors for bone engineering applications (Idowu, Cama, Deb, & Di Silvio, ; J. Liu, Chen, Zhao, & Xu, ; X. Liu, Wang, et al, ; Sladkova et al, ; Wang et al, ). In particular, human induced pluripotent stem cells (iPSCs) can be derived from every patient, proliferate indefinitely, and give rise to all cells constituting the bone tissue (Takahashi et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, they compared osteogenic potential of bone marrow derived iPSCs while cultured on the modified CPC by five biofunctional agents such as RGD, fibronectin, fibronectin‐like engineered polymer protein, ECM Geltrex, and platelet concentrate, and they results were demonstrated that modified CPC have a great osteogenic potential in comparison to the CPC, among the modified CPC, almost all osteogenic markers were increased in the fibronrctin‐CPC, Platelet‐CPC, and RGD‐CPC groups compared to the other without significantly differences [TheinHan et al, ]. This scaffold was also used in another study to evaluation of osteogenic differentiation and mineralization detection by culture of NEL‐like protein‐1 overexpressed iPSCs‐MSCs, and their results were shown that overexpressed stem cells have been shown significantly higher osteogenic gene markers and mineralization assays and the authors suggest this stem cell‐scaffold construction for used in bone tissue engineering applications [Liu et al, ].…”
Section: Methodsmentioning
confidence: 99%
“…Here, the authors reported that polyethersulfone scaffolds seeded with iPSCs induced greater bone regeneration than scaffold alone [62], results which have also been replicated in periodontal bone regeneration [63]. Furthermore, Liu recently reported that NELL1 (which encodes a protein involved in cell growth regulation and differentiation) overexpression greatly enhanced the osteogenic differentiation and mineral synthesis of iPSC-MSCs on Arg-Gly-Asp-grafted calcium phosphate cement scaffold [64]. Ideally, implementing the many arms of tissue engineering, the design of simple and robust biomaterials with an innate ability to induce lineage-specificity of iPSCs is desirable for effective clinical implementation of iPSC-based bone tissue engineering.…”
Section: Stem/progenitor Cells Applicable To Bone Tissue Engineeringmentioning
confidence: 99%